Attitudinal factors, financial literacy, and stock market participation. Issue 5 (3rd July 2017) - Sivaramakrishnan, Sreeram; Srivastava, Mala; Rastogi, Anupam
Abstract : Purpose: The purpose of this paper is to study the influence of factors such as financial literacy on a consumer's investment decisions, particularly in the stock market. Based on two empirical studies, the theory of planned behaviour (TPB) was used to understand stock market participation (SMP) in India while developing a model to represent the relationships between the various factors. Consumer financial literacy was conceptualised to be a part of perceived behavioural control and included in the TPB. Design/methodology/approach: A mixed methods research was followed where qualitative research preceded a quantitative survey-based study. In-depth interviews were conducted with investors and experts, results of which, when combined with the literature review, revealed seven variables including financial literacy which were pooled into three distinct groups based on the TPB. Responses obtained from 506 retail investors from four cities in India were analysed. Structural equation modelling was used to test the models and arrive at a final empirical model. Findings: Results of the study indicated that investment intention predicts actual investments in the stock market (which represented behaviour). Financial literacy – both subjective and objective – were also found to be significant influencers on intention while only objective financial literacy seemed to affect behaviour. Three variables – perception of regulator, risk avoidance, and hassle factor – were combined to form a second-order construct which was named "Attitude to Investment Behaviour". This had a negative impact on intention to invest in the equity markets. Financial well-being seemed to have a negative impact on intention while having a positive relationship with behaviour. Practical implications: The results present significant investor behaviour and policy implications for financial services marketing. Some interventions, especially in the area of consumer financial literacy, are more likely than others to help consumers bridge the gap between non-participation and participation in the stock market. Originality/value: The study makes a contribution to investor behaviour theory in the form of a comprehensive model to explain SMP in an emerging market. This can be further tested across geographies.